A Consortium Approach to Competency‑based Undergraduate Medical Education in Uganda: Process, Opportunities and Challenges - Kiguli, Sarah; Mubuuke, Roy; Baingana, Rhona; Kijjambu, Stephen; Maling, Samuel; Waako, Paul; Obua, Celestino; Ovuga, Emilio; Kaawa‑Mafigiri, David; Nshaho, Jonathan; Kiguli‑Malwadde, Elsie; Bollinger, Robert; et al. (Educ Health, 2014)
Uganda, like the rest of Africa, is faced with serious health challenges including human immunodeficiency virus infection/ acquired immunodeficiency syndrome (HIV/AIDS), other infectious diseases and increasing non‑communicable diseases, yet it has a significant shortage of health workers. Even the few health workers available may lack desired competencies required to address current and future health challenges. Reducing Uganda’s disease burden and addressing health challenges requires Ugandan medical schools to produce health workers with the necessary competencies. This study describes the process which a consortium of Ugandan medical schools and the Medical Education Partnership for Equitable Services to all Ugandans (MESAU) undertook to define the required competencies of graduating doctors in Uganda and implement competency‑based medical education (CBME).
Keywords: Competency‑based medical education; Consortium approach; Undergraduate education